Dinamika Perkembangan Pondok Pesantren di Era Globalisasi: Analisis Tren dan Implikasinya terhadap Pendidikan Diniyah (Studi Kasus di Pondok Pesantren Bina Insan Pangkalan Bun) - Ciptadi, Teguh; Tobroni, Tobroni (Jurnal Ilmiah Global Education, 2025)
This study examines the dynamics of adaptation of the Bina Insan Pangkalan Bun Islamic Boarding School in the era of globalization which faces curriculum dualism between traditional memorization and digital literacy. The purpose of the study is to identify structural and curricular development trends, analyze the implications for the effectiveness of early childhood education, and formulate recommendations for the integration of traditional values and modern competencies. The qualitative method of case studies was used with interview, observation, and documentation techniques. Primary data was obtained from the head of the Islamic boarding school, caregivers, teachers, students, parents, and administrative staff; Secondary data includes pesantren literature and syllabus. The results show the formation of a hybrid learning ecosystem that combines the yellow book with the creation of digital da'wah content. In conclusion, the integration of a hybrid curriculum increases the relevance and quality of early childhood education in the era of globalization.